Secretion of recombinant xylanase in Lactococcus lactis using signal peptides Usp45 and Spk1 - Roslan, Abdullah Munir; Mustafa Kamil, Afiqah; Chandran, Carumathy; Ai, Adelene Lian Song; Yusoff, Khatijah; Abdul Rahim, Raha (Springer, 2020)
Objective The effect of two signal peptides, namely Usp45 and Spk1 on the secretion of xylanase in Lactococcus lactis was analysed.